Hydraulic capability of main drainage system in city-core and eastern sub-urban Bangkok - Thin Thin Aung; Sutat Weesakul; Tawatchai Tingsanchali; Eckhardt, Ing Heinz; Kazama, So; DAAD (Bangkok : Asian Institute of Technology, 1998)
Bangkok, the capital of Thailand, is located in the lower Chao Phraya river delta with flat ground elevation of 1-2 m M.S.L. Due to the rapid urbanization in Bangkok, the existing drainage systems cannot work effectively. Therefore, an assessment of capability of main drainage system was carried out in the city-core and eastern sub-urban of Bangkok. Since, the city-core is the main Central Business District (CBD) of Bangkok and hence its drainage system is more impo1tant to analyze than others. The study area is located on the east bank of Chao Phraya river within the territory of the Bangkok Metropolitan Administration (BMA). It covers about 650 km 2 {u2022} In this study, SWMM software package was applied to simulate the flow discharges (in the channel and) flow depth (at the junctions ) at any time. The model has two programs for runoff (RUNOFF block) and complex network of open channel flow (EXTRAN block). The result from the first block are input into the second block to simulate water level variation with time at any node. Schematizing the channel network into 15 8 number of nodes, 179 numbers of branches with seven outlet boundary nodes located along the Chao Plll'aya river. The calibration of ldong network was carried out for the first time with the recent 15 minutes rainfall data. With future land use, total surcharged time increased by 2 times and flooded time increased by 1.65 times for 5 years returns periods compared with 2 years return periods. The total maximum volume is reduced by 75 % for 2 years return periods and nearly 50 % for 5 years return periods comparing with existing drainage system for klong's improvement work. When main pumping station is out of order, total maximum volume is increased by double for 2 years return periods and 1.6 times for 5 years return periods comparing with existing drainage system.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Urban runoff -- Thailand -- Bangkok